Power of desire: the politics of sexuality - Snitow, Ann (ed.); Stansell, Christine (ed.); Thompson, Sharon (ed.) (Delhi, 2009)
This provocative anthology brings together a diverse group of wellknown feminist and gay writers, historians, and activists. They are concerned not only with current sexual issues EUR abortion, pornography, reproductive and gay rights EUR but they also raise a host of new issues and questions: How, and in what ways, is sexuality political? Is the struggle for sexual freedom a complement to other struggles for liberation, or will it detract from them? Has the sexual revolution diminished or enriched the lives of women? Do womens and mens erotic natures differ fundamentally? How do race, class, and ethnicity shape sexuality? And finally, what is the best way to organize politically around sexual issues? Through history, sociology, journalism, fiction, and poetry, the collection thus addresses itself to our sexual futures: how can we build an erotic world that feminists will desire?
Keywords: Sexual revolution